2020
DOI: 10.1021/acs.jpcc.9b11170
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Novel Conjugated Nanohoops: Revealing the Effects of Topology and Size

Abstract: The unique properties of chemical materials are usually related to the topology and size of their constituent unit. Inspired by a previous report on the synthesis of a separable catenane composed of two Mobius-conjugated nanohoops, we theoretically predicted the optical properties of the Mobius monomer, its Huckel analogue, and some structures derived from them. The underlying reasons for the effects of topology and size on molecular (hyper)polarizability and the absorption spectrum were explored from the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 50 publications
5
65
0
Order By: Relevance
“…There is no significant difference between the α iso of Li@C 18 in and Li@C 18 out , which is similar to the law of polarizability between the analogues of many other types of compounds we have studied [41][42][43][44]. However, the change in the way of binding of Li atom not only causes the magnitude of β vec to vary, but also alters the sign of it.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexessupporting
confidence: 67%
See 1 more Smart Citation
“…There is no significant difference between the α iso of Li@C 18 in and Li@C 18 out , which is similar to the law of polarizability between the analogues of many other types of compounds we have studied [41][42][43][44]. However, the change in the way of binding of Li atom not only causes the magnitude of β vec to vary, but also alters the sign of it.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexessupporting
confidence: 67%
“…The (hyper)polarizability density analysis, which graphically exhibits the spatial contribution of electrons in a molecule to electric response properties, is helpful to gain a deep insight into the physical nature of molecular (hyper)polarizability [17,[41][42][43][44]. The (hyper)polarizability densities, namely the local contributions to the respectively, for comparison.…”
Section: (Hyper)polarizabilities Of Li@c 18 Complexesmentioning
confidence: 99%
“…Therefore, the field of optical materials has been exploring how to develop new compounds with tunable photophysical properties or enhanced (hyper)polarizabilities for a long time. [4][5][6] So far, researchers have successfully recognized a variety of molecules with exciting optical properties, including inorganic complexes, [7][8][9] organic molecules, [10][11][12][13] metal clusters, 14,15 doped polarizable electrides, 16,17 and even macrocyclic compounds with special topology, 6,18,19 and applied some of them into practice. Among them, the conjugated organic chromophores with electron donating and electron accepting groups at both ends were one of the most popular optical units, partially due to their convenient structural tailoring.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of (hyper)polarizability density is helpful in understanding the physical essence of molecular (hyper)polarizability. 25,26,50 The integrand functions of the (hyper)polarizability densities, that is, the local contributions of the (hyper)polarizability, in z direction [ (1) It was observed that except for the distinguishable differences near the electrondonating group, the (1) Displayed in Figure S4 are the local contribution functions of the molecular (hyper)polarizability in x axis of the studied mesoionic compounds under the zerofrequency field. It can be clearly seen that in the isosurface of every order local contributions of the (hyper)polarizability, both the positive and the negative contributions increase with the electron-donating capacity within the molecule.…”
Section: (Hyper)polarizability Density Analysesmentioning
confidence: 99%